2007
DOI: 10.1300/j030v16n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Color of Raw, Frozen, and Smoked Fillets of Rainbow Trout (Oncorhynchus mykiss) Fed Diets Supplemented with Astaxanthin and Saponified Red Chilli (Capsicum annuum) Extracts

Abstract: Rainbow trout (Oncorhynchus mykiss) were fed diets supplemented with astaxanthin and saponified red chilli extracts. Raw fillets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For example, it was found that capsicum oil (1 mg/kg) had positive impacts on growth, hematological parameters, and serum biochemical indices in trout fries (Parrino et al, 2020). Moreover, the dietary impacts of saponified C. annuum extract (Arredondo‐Figueroa et al, 2007) and CAO (Ingle de la Mora et al, 2006) on the pigmentation and fillet color of rainbow have been demonstrated. Dietary supplementation with paprika oleoresin (60 mg/kg) induced good coloration of ornamental dwarf cichlid (Harpaz & Padowicz, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was found that capsicum oil (1 mg/kg) had positive impacts on growth, hematological parameters, and serum biochemical indices in trout fries (Parrino et al, 2020). Moreover, the dietary impacts of saponified C. annuum extract (Arredondo‐Figueroa et al, 2007) and CAO (Ingle de la Mora et al, 2006) on the pigmentation and fillet color of rainbow have been demonstrated. Dietary supplementation with paprika oleoresin (60 mg/kg) induced good coloration of ornamental dwarf cichlid (Harpaz & Padowicz, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Rainbow trout flesh will typically be less reddish or whitish when the diet is not supplemented with carotenoids, as salmonids cannot synthesize carotenoids de novo [ 16 ]. Atlantic salmon and rainbow trout fish fed an unpigmented diet yield fillets with higher L* (lightness) and lower a* (redness) and b* (yellowness) values in comparison to fish on astaxanthin-supplemented diets [ 17 , 18 ]. Brown et al [ 19 ] reported a significant difference in the color retention indices (ECI, hue, and chroma) of fillets from rainbow trout fish that never received dietary astaxanthin compared to fillets from fish that received an astaxanthin-supplemented diet.…”
Section: Introductionmentioning
confidence: 99%